2021
DOI: 10.3389/fcell.2021.663279
|View full text |Cite
|
Sign up to set email alerts
|

Reck-Notch1 Signaling Mediates miR-221/222 Regulation of Lung Cancer Stem Cells in NSCLC

Abstract: Cancer stem cells (CSCs) contribute to the cancer initiation, metastasis and drug resistance in non-small cell lung cancer (NSCLC). Herein, we identified a miR-221/222 cluster as a novel regulator of CSCs in NSCLC. Targeted overexpression or knockdown of miR-221/222 in NSCLC cells revealed the essential roles of miR-221/222 in regulation of lung cancer cell proliferation, mammosphere formation, subpopulation of CD133+ CSCs and the expression of stemness genes including OCT4, NANOG and h-TERT. The in vivo anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Cancer stemness is closely related to the occurrence and metastasis of NSCLC 17 . To investigate the effect of αPD‐L1 on stemness of NSCLC cells by regulating TAM/M2 polarization, the protein expression of stemness‐related markers, including CD44, Oct4, Sox2, Bmi‐1 and Nanog were detected by the western blot assay (Figure 5A–C,E–G; Figure S1K‐M).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer stemness is closely related to the occurrence and metastasis of NSCLC 17 . To investigate the effect of αPD‐L1 on stemness of NSCLC cells by regulating TAM/M2 polarization, the protein expression of stemness‐related markers, including CD44, Oct4, Sox2, Bmi‐1 and Nanog were detected by the western blot assay (Figure 5A–C,E–G; Figure S1K‐M).…”
Section: Resultsmentioning
confidence: 99%
“…Cancer stemness is closely related to the occurrence and metastasis of NSCLC. 17 To investigate the effect of αPD‐L1 on stemness of NSCLC cells by regulating TAM/M2 polarization, the protein expression of stemness‐related markers, including CD44, Oct4, Sox2, Bmi‐1 and Nanog were detected by the western blot assay (Figure 5A–C,E–G ; Figure S1K‐M ). The results showed that the protein expression of stemness‐related markers was up‐regulated after TAM/M2 polarization induced by IL‐13 or NSCLC cells, while αPD‐L1 inhibited this phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Many miRNAs have important roles in the occurrence, progress, and metastasis of lung cancer through regulating a variety of processes, including cancer initiation and progression. Some miRNAs associated with prognostic value have been discovered thus far, such as miR-221 [ 19 ], miR-372 [ 20 ], miR-429 [ 21 ], miR-486 [ 22 ], and miR-137 [ 23 ]. However, many miRNAs are yet to be discovered in LUAD, and their roles are yet to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, new discoveries suggest that it may have a role as a cancer biomarker 89 . A cluster of miR‐221/222 has been identified as a marker for breast cancer 90–93 as well as other cancers such as colorectal, glioma, glioblastoma, and lung 49,94–96 . Researchers have also discovered its significance in relation to FLD.…”
Section: Noncoding Rnas and Nafldmentioning
confidence: 99%
“…89 A cluster of miR-221/222 has been identified as a marker for breast cancer [90][91][92][93] as well as other cancers such as colorectal, glioma, glioblastoma, and lung. 49,[94][95][96] Researchers have also discovered its significance in relation to FLD. In 26 individuals with NASH, Ogawa et al 97 detected a significantly elevated level of miR-221/222.…”
Section: Mirna and Nafldmentioning
confidence: 99%